Application Quality Dominates Gopay User Trust in Surabaya: Kualitas Aplikasi Menjadi Faktor Utama dalam Kepercayaan Pengguna Gopay di Surabaya - Lendra, Ray (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid expansion of digital wallet services has increased the importance of user trust in sustaining digital payment adoption and usage. Specific Background: In Indonesia, competition among e-wallet platforms such as GoPay, OVO, DANA, and ShopeePay has intensified, positioning brand image, perceived security, and application quality as key determinants of user trust. Knowledge Gap: Previous studies have produced inconsistent findings and predominantly examined these variables separately, leaving limited understanding of their simultaneous and relative contributions to user trust in digital wallet services. Aims: This study analyzes the associations of brand image, perceived security, and application quality with user trust among active GoPay users in Surabaya and identifies the most dominant factor shaping trust. Results: Using a quantitative survey approach with 160 active GoPay users and multiple linear regression analysis, the findings reveal that brand image, perceived security, and application quality all show significant positive associations with user trust (p < 0.05). Among these variables, application quality demonstrates the strongest influence, indicated by the highest standardized regression coefficient (β = 0.418), followed by perceived security and brand image. The model also explains a substantial proportion of variance in user trust. Novelty: This study integrates brand image, perceived security, and application quality within a single analytical framework while demonstrating the dominant role of application quality in digital wallet trust formation. Implications: The findings indicate a shift from perception-based trust toward experience-based trust, suggesting that digital wallet providers should prioritize application reliability, usability, responsiveness, and system performance to sustain user trust and competitiveness in digital financial services. Highlights: System reliability and usability emerged as the strongest determinant of trust formation among GoPay users. Transaction safety and data protection remained significant considerations in digital payment adoption decisions. Direct interaction with fintech platforms became more central than symbolic reputation in evaluating service credibility. Keywords: User Trust, Brand Image, Perceived Security, Application Quality